Use of flaps in inguinal lymphadenectomy in metastatic penile cancer - Azevedo,Roberta Alvares (2021)
ABSTRACT Purpose: Reviewing surgical procedures using fasciocutaneous and myocutaneous flaps for inguinal reconstruction after lymphadenectomy in metastatic penile cancer. Material and Methods: We reviewed the current literature of the Pubmed database according to PRISMA guidelines. The search terms used were “advanced penile cancer”, “groin reconstruction”, and “inguinal reconstruction”, both alone and in combination. The bibliographic references used in the selected articles were also analyzed to include recent articles into our research. Results: A total of 54 studies were included in this review. About one third of penile cancers are diagnosed with locally advanced disease, often presenting with large lymph node involvement. Defects in the inguinal region resulting from the treatment of metastatic penile cancer are challenging for the surgeon and cause high patient morbidity, rendering primary closure unfeasible. Several fasciocutaneous and myocutaneous flaps of the abdomen and thigh can be used for the reconstruction of the inguinal region, transferring tissue to the affected area, and enabling tensionless closure. Conclusions: The reconstruction of defects in the inguinal region with the aid of flaps allows for faster postoperative recovery and reduces the risk of complications. Thus, the patient will be able to undergo potential necessary adjuvant treatments sooner.